Effects of herbal dregs supplementation of Salvia miltiorrhiza and Isatidis Radix residues improved production performance and gut microbiota abundance in late-phase laying hens - Li, Zhaonian; Ma, Ning; Gong, Xincheng; Shi, Wanyu; Meng, Xianhua; Yan, Jingjiao; Zhao, Zhiqiang; Li, Jiefeng (Frontiers in Veterinary Science, 2024)
The present study was designed to evaluate the effect of a mixture of Chinese medicinal residues (CMRs) consisting of Salvia miltiorrhiza residues (SMR) and Isatidis Radix residues (IRR) on productive performance, egg quality, serum lipid and hormone levels, liver and blood antioxidant capacity, oviduct inflammation levels, and gut microbiota in the late-laying stage. A total of 288 fifty-four-week-old BaShang long-tailed hens were divided into four groups. The feed trial period was 8 weeks. The control group was fed the basic diet as a CCMR group, supplemented with 3, 4, and 6% for the experimental groups LCMR, MCMR, and HCMR. The egg production rate of the MCMR group was 8.1% higher than that of the CCMR group (p < 0.05). Serum triglyceride (TG) levels of hens of the CMR-supplemented group were significantly decreased than those of the CCMR group (p < 0.05). The group supplemented with different levels of CMR had significantly higher serum HDL-C levels compared with the control group (p < 0.05). Follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels were remarkably increased for the LCMR and MCMR groups and significantly decreased for the HCMR group compared to CCMR (p < 0.05). Serum and liver glutathione peroxidase (GSH-PX) activities were significantly increased, and malondialdehyde (MDA) levels were significantly decreased in the MCMR group compared to the CCMR group (p < 0.05). The expression levels of tubal inflammatory factor markers (IL-4, IL-1β, TNF-α) in the MCMR and HCMR groups were consistent with the pathological findings of the sections. As for cecal microbiota, supplementation with CMR affected the alpha diversity of the cecum microbiome at the genus level. The Shannon index was significantly higher in the MCMR group than in the CCMR and HCMR groups (p < 0.05). Supplementation with different levels of CMR mainly regulated the ratio of intestinal Firmicutes to Bacteroidetes and the abundance of phyla such as Proteobacteria. In addition, CMR supplementation at different levels in the diet enriched lipid-metabolizing bacteria, such as Bacteroides and Ruminococcus_gnavus_group. Furthermore, according to linear discriminant analysis (LDA) effect size (LEfSe) analysis, the MCMR group showed an increase in the number of short-chain fatty acid-producing bacteria Romboutsia and fiber-degrading specialized bacteria Monoglobus. Therefore, supplementation of appropriate amounts of CMR to the diet of laying hens enhanced reproductive hormone levels, hepatic antioxidant capacity, and lipid metabolism, alleviated the levels of oviductal inflammatory factors, and modulated the abundance structure of bacterial flora to improve the late-laying performance and egg quality. The results of the current study showed that CMR is a beneficial feed supplement for chickens when added in moderation.